Do Families Attitudes and Behaviors Support Sustainable Water Consumption - Aydiner Boylu, Ayfer; Gunay, Gulay (European Journal of Sustainable Development, 2017)
For increasing the quality of life and sustainable improvement, the importance of reaching for drinkable, usable and clean water sources in the 21st century has increased and started to become a significant potential problem to be solved in the World. With today's busy lifestyles, people are often unaware of the amount of water they consume. With the acceleration of modern life, individuals often choose the solution that best suits their time and convenience, rather than optimizing for efficiency and environmental outcomes, since they do not find water-related activities important. Water, which is naturally regarded as an inexhaustible source, is gradually decreasing over time and disappearing day by day. Therefore this research has been planned to determine individuals’ water consumption behavior at homes regarding the effective and efficient use of water sources. The sample comprised 654 individuals who resided in Safranbolu, Turkey. Data were collected through a demographic information form, Attitudes Toward Water Use (AtWC), Water Saving Behavior at the Home (WSBQ) and Sustainable Consumption Behavior Scale (SCBs). To determine the factors affecting water saving behavior at the home, correlation and hierarchical regression analyses were employed. Pearson correlation analyses revealed significant positive relationship between sustainable consumption behavior (SCBs) and saving behavior at the home (WSBQ) (r=.43; p<0.01), attitudes toward water use (AtWC) and saving behavior at the home (WSBQ) (r=.24; p<0.01). Hierarchical multiple regression analysis displayed that water saving behavior at home is influences by sustainable consumption behavior and attitudes toward water conservation. The theoretical implication of this study helps to understand the basic concepts of water saving behavior. Keywords: Households, attitudes toward water use, water saving behavior, sustainable consumption behavior